2015
DOI: 10.4038/tar.v26i1.8073
|View full text |Cite
|
Sign up to set email alerts
|

Effect of root or foliar application of soluble silicon on plant growth, fruit quality and anthracnose development of capsicum

Abstract: This study was conducted to investigate the root and foliar application of soluble silicon on plant growth, fruit quality parameters and anthracnose disease development in fruits of Capsicum annuum L. 'Muria F1'. Silicon as potassium silicate (75 mg/l) was provided to root by amending the nutrient solution (T Root) at weekly interval or to foliage by spraying (T Foliar) daily, as two separate treatments. Control plants were not treated with Si. Disease resistance in fruits was assessed by artificial inoculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Exogenous foliar application of potassium silicates (K 2 SiO 3 ) has been used for disease control in various crops, [2][3][4][5][6][7][8][9] including grapes [10]. These treatments do not improve plant growth or yield; although some differences might have been observed due to indirect effects resulting from the lower infestation of disease causing agents, or due to the presence of some agents within silicates material spray formulations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous foliar application of potassium silicates (K 2 SiO 3 ) has been used for disease control in various crops, [2][3][4][5][6][7][8][9] including grapes [10]. These treatments do not improve plant growth or yield; although some differences might have been observed due to indirect effects resulting from the lower infestation of disease causing agents, or due to the presence of some agents within silicates material spray formulations [11].…”
Section: Introductionmentioning
confidence: 99%
“…Potassium silicate provides an excellent source of soluble silicon for plants and also provides supplemental potassium, a plant macronutrient (Jayawardana et al, 2014). Potassium silicate is used to strengthen plant resistance to pathogens and to enhance agricultural productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Also, they measured silicate-treated leaves and found that leaves treated by silicate were harder than control leaves. Moreover, Jayawardana et al (2014) reported that the root and the foliar application of soluble silicon as potassium silicate caused decrease in disease incidence and increase in plant growth and fruit quality parameters. Weerahewa and David (2015) tested tomato cultivars "Thilina" and "Maheshi" by soil application of silicon at 0, 50, and 100 mg/l during the growth stage, flowering stage, and both growth and flowering stages to control anthracnose.…”
Section: Discussionmentioning
confidence: 99%